Cx43- and Smad-Mediated TGF-β/ BMP Signaling Pathway Promotes Cartilage Differentiation of Bone Marrow Mesenchymal Stem Cells and Inhibits Osteoblast Differentiation - Ya-Dong Zhang; Shi-Chang Zhao; Zhong-Sheng Zhu; Yi-Fei Wang; Jian-Xiang Liu; Zhi-Cai Zhang; Feng Xue (Cellular Physiology and Biochemistry, 2017)
Background/Aims: The aim of this study was to investigate the influence of Cx43- and Smad-mediated TGF-β/BMP signaling pathway on the differentiation of bone marrow mesenchymal stem cells (BMSCs) into cartilage and inhibition of ossification. Methods: BMSCs of Wistar rats were cultured and assigned into 5 groups for transfection with adenoviruses. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were employed to detect mRNA and protein expressions of target genes. The condition of cartilage and ossification were measured by a series of staining methods. Subcutaneous injection of mesenchymal stem cells (MSCs) into nude rats was performed. Results: After transfection, compared to the AdGFP group, the corresponding target mRNAs were overexpressed in the AdBMP2, AdSmad1, AdCx43 + AdSmad1 and AdCx43 + AdSmad1 + AdBMP2 groups, and overexpression of BMP2 at the mRNA and protein expression was observed in the AdSmad1 and AdCx43 + AdSmad1 groups. The mRNA expressions of aggrecan (ACAN) and collagen type II alpha 1 (Col2a1), the glycosaminoglycan content of the extracellular matrix and the expression of type II collagen, Col2a1, osteopontin (OPN) and osteocalcin (OC) were higher in the AdBMP2, AdSmad1, AdCx43 + AdSmad1 and AdCx43 + AdSmad1 + AdBMP2 groups than in the AdGFP group; alkaline phosphatase (ALP) activity and mRNA and protein expressions of Runx2 were also higher in these groups than in the AdGFP group. Heterotopic osteogenesis tests demonstrated evident cartilage differentiation ability in the AdCx43 + AdSmad1 + AdBMP2 groups. In comparison, the AdCx43 + AdSmad1 and AdSmad1 groups exhibited weaker cartilage differentiation abilities. Conclusion: Cx43 and Smad1 promote BMP-induced cartilage differentiation of BMSCs and inhibit osteoblast differentiation, which provide a new strategy for cartilage tissue engineering using exogenous Cx43 and Smad1.